Revision of Whitehouse's eocrinoids Peridionites and Cymbionites, with description of the associated fauna including two new echinoderm genera, lower Middle Cambrian Thorntonia Limestone, northwestern Queensland. Issue 1 (2nd January 2021) - Jell, Peter A.; Sprinkle, James
Abstract: The section in the lower middle Cambrian Thorntonia Limestone one kilometre south of Thorntonia Homestead, described by Whitehouse (1940, 1941), has been re-investigated using acid-etching techniques. Thousands of variously silicified bioclasts etched from this section are the basis of this study. The echinoderms Cymbionites Whitehouse, 1941 and Peridionites Whitehouse, 1941 are shown to be basal circlets of stalkless, multicirclet, epispire- and brachiole-bearing eocrinoids. These two genera appear most closely related to Lichenoides Barrande from the Czech Republic. A stalked eocrinoid, Thorntonites dowlingi gen. et sp. nov., and an edrioblastoid, Ikerus edgari gen. et sp. nov., occur with Peridionites higher in the section than Cymbionites . Thorntonites has a multimeric stalk and fused conical holdfast, at least three circlets of thecal plates with fewer and coarser epispires, and larger brachioles around the summit. Ikerus has a multimeric stalk, three circlets of thecal plates and straight ambulacral grooves, without connection to the thecal interior, traversing the central axis of thecal plates. These three eocrinoids and the edrioblastoid occur in shallow-water carbonates as abundant, low-to-medium tier, suspension feeders associated with brachiopods, molluscs, hyoliths, sponges, edrioasteroids and trilobites. This associated fauna includes Xystridura cf. negrina, Xingrenaspis cf. tongshanensis, Diraphora dyunyin, Westonia nyapungensis, Latouchella accordionata and Guduguwan hardmani, which collectively allow correlation with the Xystridura negrina assemblage. * Peter A. Jell [amjell@bigpond.com ], School of Earth Sciences, University of Queensland, St Lucia, Queensland 4072, Australia; James Sprinkle [echino@jsg.utexas.edu ], Department of Geological Sciences, Jackson School of Geosciences, University of Texas, 1 University Station C1100, Austin, TX 78712-0254, USA .